Practice on Metered Dose Inhaler Techniques and Its Associated Factors among Asthmatic Patients at Debre Markos Comprehensive Specialized Hospital, East Gojjam, Ethiopia: A Prospective Study - Tadele Asmare; Anteneh Belayneh; Bekalu Dessie (The Scientific World Journal)
Background. Asthma stands 16th among the leading causes of years lived with disability and 28th among the leading causes of disease in the world. A metered-dose inhaler remains the principal route for drug administration, and it has greater advantages over systemic treatment. In routine use, however, a majority of patients make inhalation errors. Suboptimal inhaler technique worsens health outcomes, with poor disease control, and increases the risk of hospitalization. This study aimed to assess practice metered-dose inhalation techniques and associated factors among asthmatic patients at Debre Markos Comprehensive Specialized Hospital, East Gojjam, Amhara region, Ethiopia. Methods. Prospective cross-sectional study was conducted from July 15 to August 30, 2020. Data were collected through a semistructured questionnaire. The data were analyzed using SPSS version 25. Associations between dependent and independent variables were assessed by using binary and multiple logistic regressions. P values less than 0.05 were considered to be statistically significant in all cases. Results are presented in tables, figures, numbers, and percentages. Result. A total of 166 patients had involved in the study, of which 52.4% were females. One hundred and eleven (66.9%) participants had good knowledge of asthma and inhalational techniques, while the rest of them had poor knowledge. One hundred and eight (65.1%) patients had effective practice on metered-dose inhaler use techniques. Participant's knowledge regarding asthma and meter dose inhaler and marital status has a significant association with their practice of metered-dose inhaler techniques with P value 0.001 and 0.006, respectively. Conclusion. In this study, most participants are suffering from asthma for a long duration and they have repeated exacerbation. Around two-thirds of patients had good knowledge regarding asthma and metered-dose inhaler and practice on metered-dose inhaler techniques. Participants with poor knowledge had poor practice on metered-dose inhaler techniques, and single patients were less likely to have poor practice on metered-dose inhaler techniques. Health education and counseling services should be consistently provided to the clients regarding the proper steps of inhalers use.